The Effect Of Using Audiovisual Media On Learning Outcomes In “Indonesia Hebat” Children’s Rhythmic Gymnastics Among Year 4 Pupils - Misqola Famay Azzahra; Tubagus Herlambang; Pandu Kresnapati (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
Rhythmic gymnastics learning in primary schools often faces challenges such as low student interest, boredom, and suboptimal learning outcomes due to monotonous teaching methods. This study aims to determine the effect of audiovisual media on learning outcomes (psychomotor, affective, and cognitive aspects) in rhythmic gymnastics among Year 4 pupils at SDN 01 Bukur. This research employed a pre-experimental design with a quantitative approach (one-group pretest-posttest). The subjects were 22 Year 4 pupils selected through total sampling. Data were collected through tests and observations and then analyzed using descriptive statistics, normality tests, paired sample t-tests, the Wilcoxon Signed Rank Test, and N-Gain analysis. The results revealed significant improvements in all three aspects. Psychomotor scores increased from 58.91 to 86.32 (N-Gain 0.66/moderate-high). Affective scores increased from 69.09 to 88.18 (N-Gain 0.58/moderate). Cognitive scores increased from 76.59 to 81.95 (N-Gain 0.15/low). Statistical tests validated significant differences between pretest and posttest (p < 0.05 for all aspects). In conclusion, the use of audiovisual media has a positive and significant effect on rhythmic gymnastics learning outcomes, particularly in psychomotor and affective aspects. Audiovisual media is recommended as an innovative and interactive learning strategy for physical education in primary schools